(untitled) (TAJ: Journal of Teachers Association, 2018)
Background: Breast cancer is a common form of cancer among women globally. Bone is the most common site to which breast cancer metastasizes. Between 30% and 85% of patients with metastatic breast cancer will develop bone metastases during the course of the disease. Objective: To evaluate the pattern and distribution of skeletal metastases in different clinical stages of breast cancer patients by using Tc-99m MDP bone scan. Materials and methods: A retrospective study was conducted on 305 consecutive female breast carcinoma patients referred for bone scan to Institute of Nuclear Medicine and Allied Sciences, Rajshahi from January 2015 to June 2017. All patients were categorized in one of the three groups; early breast cancer (EBC, comprises clinical stage I and II), locally advanced breast cancer (LABC, clinical stage III) and metastatic breast cancer (MBC, clinical stage IV). Bone scan was performed by an intravenous bolus injection of 20 mCi Tc99m-MDP and bone phase images were taken at three hours after injection of the radiotracer. Results: Out of 305 studied patients, 16 patients (5.25%) were in EBC group, LABC patients were 173 (56.72%) and MBC were 116 (38.03%). 98 patients (32.13%) were positive for skeletal metastases. In 16 EBC patients only 01 patient (6.25%) had skeletal metastasis in thoracic spine. Skeletal metastases were 20.81% in LABC and 52.59% in MBC group. Thoraco-lumbar spine was the commonest site in both groups followed by ribs, pelvic bones, upper and lower extremities, cervical spine, sternum, scapula and skull bone. Conclusion: Bone scan should be done in all LABC and MBC patients and in symptomatic EBC at disease presentation. Parts of bone to focus are thoracic and lumbar spine in all stages, followed by ribs, pelvis and extremities. Tc-99m MDP bone scan play a major role in early detection of skeletal metastasis in breast cancer patients. TAJ 2017; 30(2): 47-53